The Impact of the Poet’s culture on Building his Artistic Output: A Study in the Light of the Semiotics of Culture The Egyptian Essam Abdel Mohsen as a Choice - Al-Fadhli, Dr. Jawad Hadi Hussein (Thi Qar Arts Journal, 2022)
Poet's culture is one of the important pillars of the artistic output that the creator seeks to produce in the most beautiful image of the recipient in order to gain his interaction and acceptance of the creative text, by spreading cultural signals that establish a central focus in reading the artwork, and excite its potential to the reader, to be another effective product and receive the desired message from the work, which is the focus of the author’s interest in Build his creative text.The research is based on an introduction that we dealt with; in which we dealt with culture in general, and the culture of the poet and its impact on the distinction of its owner over his peers through its knowledge and cultural storage. Semiotics, the history of its development, and the most prominent founders of this modern science. As for the second topic, he explored the religious culture references and their impact on building the literary text, and how the creator dealt with them in bringing out their common potentials together for a reader. In the elucidation of the understanding of the other through the existing commonalities between them, these contents scattered in his work, and as for the fourth topic, it revealed the effect of the literary culture references in the statement of the text and revealed its desired goals from it in understanding and clarifying its contents. Poet rich in semiotic signs diverse culture.